E-Training System To Improve HR Capability at Indofood Factory Using Codeigniter Framework - fifit alfiah; Faiz Muhammad Syam; Dini Anggrayni (ADI Publisher, 2022)
Digital developments on a global scale are now growing very rapidly, especially with the emergence of a covid-19 pandemic that has made all institutions, both education, offices and various other types of institutions, begin to adapt to the use of computers and mobile phones, where everything is based on IoT Internet of Thing, namely all types. the activities are carried out online, besides that, there are many obstacles, such as the amount of time wasted because they have to prepare training classrooms, prepare ppt slides for each training session, and prepare training questions which will then be printed and distributed to training participants. A lot of costs and energy are wasted in conducting training, especially if you have to do training at the branch office and the work of employees is not controlled when they have to do training. For this reason, it is necessary to build an information system for the training department to provide informative training data and to automate the recording of training history. To support the program design process developed by implementing a throw-away prototype model, using the PHP programming language with CodeIgniter Framework, database design using the PostgreSQL database. With the training department information system, the process of delivering training information is faster and more informative, facilitating the process of recording employee training history, and reducing the use of paper because it is computerized making it easier to conduct training and shorten the training process